Supersaturation is a major driving force for protein aggregation in neurodegenerative diseases. (February 2015) - Ciryam, Prajwal; Kundra, Rishika; Morimoto, Richard I.; Dobson, Christopher M.; Vendruscolo, Michele
Highlights Widespread protein aggregation is observed in neurodegenerative diseases. Supersaturated proteins form a metastable sub-proteome prone to aggregation. Specific biochemical pathways are enriched in supersaturated proteins. Supersaturated pathways are associated with neurodegenerative diseases.